Sustainable tourism planning and development in a cross-border destination: the Eurocity Chaves Verín - Liberato, Dália (2022)
Tourism activities which have the highest environmental, economic, and social benefits are more sustainable. However, when the destination considers that it is still an emerging destination, it does not consider its sustainability at all levels, being only on the agenda little more than the environmental policies of solid waste and saving of natural resources. The aim of this study is to analyze the sustainable management of a border destination: The Eurocity Chaves-Verín. Sustainability is the new trend for several sectors of economic activity, without ceasing to be also for tourism. Tourism is very important for the regions, must be developed and preserved to ensure its viability over time, improve the living conditions of populations and ensure the preservation of their most valuable resources. The methodology used in this study is the qualitative methodology, through the realization of semi-structured interviews. The present study aims to understand if the management of the border destination—Eurocity Chaves Verín (ECV) foresees all the pillars of sustainability: economic, socio-cultural, and environmental, with the purpose of raising the awareness of the destination agents to the importance of sustainable management in all the pillars of sustainability, in time and space, even when it is considered that the need does not exist yet.